A reestruturação do centro comercial de Maceió - Santos, Sandra Lucia dos (2005)
Maceió was born in the 17th century along the margins of the Jaraguá port and it was growing around a sugar engenho (sugar cane processing farm) located where today is the D. Pedro II Square. The original toponymy Massayó gave the name to the small village, whose urban draw was defined by the constructions assented on the tortuous trails of the oxcarts. Thus were formed the streets of the actual downtown. On the 19th century, they got the streetcars and the train that advanced till the port. On the 20th century the architecture of central streets was diversified, showing stiles and programs conditioned by the new uses. The commerce prospered along of this century but provoked a disordered urban increase and the disconfiguration of the original architecture. The general crisis of the years 1980 installs its decadence, accelerated by the arrival of the shopping centers. The idea of the restructuration of downtown borns of the crisis, although it never has been done. However, it gets force recently, object of articulation between the private and the public actions. This fact motives this work that tries to reflect about this restructuration. The empirical research conglobates the study of the historical formation, the actual physical characterization and the knowledge of the social actors acting in downtown. The construction of an analytical chart and a diagnostic will base prospections and contributions for the revitalization and the spatial requalification intended.